MASYARAKAT MADANI DALAM KITAB NAHWA AL-MUJTAMA ISLAMI KARYA SAYYID QUTHB - Amaliah Farhan (STIT Darul Hijrah Martapura, 2021)
This study aims to examine the concept of civil society as depicted by Sayyid Qutb in the book